Effectiveness of Large-Scale Social Restrictions (PSBB) toward the New Normal Era during COVID-19 Outbreak: a Mini Policy Review - Andriani, Helen (Journal of Indonesian Health Policy and Administration, 2020)
The government of Indonesia has not used lockdown or quarantine as an option to tackle the spread of Coronavirus, as the impact of lockdown on small communities in the informal sector that lives from daily income will be severe. Alternatively, the government is enforcing Large-Scale Social Restrictions (Pembatasan Sosial Berskala Besar or "PSBB") to respond to the state of emergency in public health. Starting in June 2020, the government has implemented transitional PSBB in some red zone areas, including the capital Jakarta and East Java province, despite the surge in case numbers. This paper aims to investigate the effectiveness of the PSBB policy applied in Indonesia during the COVID-19 outbreak and the readiness to embrace the new normal, between April and June 2020, based on rapid literature analysis in a search on Medline(-Pubmed), government speeches and reports, social and mass media platforms. Implementation of PSBB is a preventive measure to combat Coronavirus’ spread in some Indonesian areas. Indonesia should not be in a “new normal” situation. The transitional PSBB phase serves as an early chapter of a new normal that would apply only to strategic sectors with manageable risks combined with better regulation and compliance by the public